Counseling and Individual Factors on Postpartum Mother to Use Contraceptive Method - Mindarsih, Theresia; Ludji, Ina Debora Ratu; Pelokilla, Marthen Robinson (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
During postpartum period, mother needs counseling on the usage of contraception tools. Contraception is needed before menstruation returns to prevent pregnancy. The purpose of this research was to investigate the influence postpartum counseling and motherÃ¢â‚¬â„¢s individual factors on contraception usage in Kupang City. This was a quasi-experimental study. 64 respondents were selected through purposive sampling and divided into 2 groups, 32 people were given counseling and 32 were not. Data was collected using questionnaires. Data analysis was bivariate and multivariate. The result showed 22 respondents (68.75%) received counseling about postpartum contraception and 8 (25%) did not. The result of chi square test showed significant value of ÃÂ = 0.000, indicating that postpartum maternal counseling influenced contraception usage. Therefore, postpartum maternal counseling affected contraception method usage by mothers in Kupang City.